Hydrogen network optimization by integrating impurity distributions of a fluid catalytic cracker and hydrogenation reaction kinetics. (10th August 2018) - Wu, Le; Liang, Xiaoqiang; Kang, Lixia; Liu, Yongzhong; Saffron, Christopher M.
Abstract: Minimizing hydrogen consumption in hydrotreating (HDT) units is increasingly important as more heavy and sour crude oil are processed in refineries. A fluid catalytic cracking (FCC) unit commonly links the vacuum gas oil HDT unit with the cracked diesel and the cracked gasoline HDT units. In the course of processing, undesired impurities, such as sulfur, nitrogen and aromatics, pass from the upstream HDT unit, to the FCC unit where they are cracked, and then to the downstream HDT units. As impurity removal can be accomplished in the upstream and downstream HDT units, it is important to understand how the interconnecting FCC unit affects impurity distributions of the adjacent HDT units when minimizing the hydrogen consumption of the whole hydrogen network. A stepwise optimization strategy, using three mathematical models (designated M1, M2 and M3), is proposed to minimize the hydrogen consumption considering impurity distributions within the FCC unit and hydrogenation reaction kinetics. By integrating the FCC unit, M1 is used to investigate the effects of the FCC unit on the upstream and downstream HDT units' purification degrees and their hydrogen consumption. Based on the hydrogenation reaction kinetics, M2 is used to optimize the operating conditions and to minimize hydrogen consumption within the HDT units according to optimal purification degrees as established by M1. M3 is a hydrogen network optimization model, which is used to obtain the optimal structure of the hydrogen network. Eco-indicator 99 was employed to evaluate the environmental impacts of the hydrogen network. Results show that the hydrogen consumption, the total annual cost (TAC) and the environmental impacts of the hydrogen network are reduced by 44.5%, 34.4% and 38.6%, respectively, compared to the original operation. Optimization without considering the FCC unit and the hydrogenation reaction kinetics only reduced by 32.6%, 19.1% and 28.2% in the hydrogen consumption, TAC and the environmental impacts. Consequently, the effects of the FCC unit and the hydrogenation reaction kinetics should be considered when optimizing the hydrogen network in a refinery. Graphical abstract: A stepwiseoptimization strategy using three mathematical models (M1, M2 and M3) is proposed to minimize the hydrogen consumption considering impurity distributions within the FCC unit and hydrogenation reaction kinetics. Image 1 Highlights: An MINLP model is proposed for hydrogen network optimization. A stepwise strategy with three sub-models is proposed to solve the MINLP model. The effect of FCC unit on hydrogen network optimization is studied. The effect hydrogenation kinetics on hydrogen network optimization is also studied.